Emergence of multidrug-resistant Candidozyma auris in southern China: a multicenter study on genetic diversity and antifungal resistance - Guo, Penghao; Fang, Jingchun; Wang, Ruizhi; Lin, Weihong; Jiang, Yueting; Long, Jun; Chen, Lingjuan; Huang, Xudong; Liao, Kang; Peng, Yaqin (Frontiers in Microbiology, 2025)
PurposeCandidozyma auris (C. auris) is an emerging fungal pathogen that is resistant to multiple drugs and poses a serious threat to global health. This study aimed to investigate the genetic diversity and antifungal resistance profiles of C. auris in southern China.MethodsA total of 108 clinical C. auris isolates were collected from eight hospitals in Guangdong Province between January 2023 and January 2024. All the isolates were identified via matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS). Phylogenetic analysis was conducted on the basis of the sequencing results of the RPB1 and D1/D2 genes. The mechanisms of resistance to fluconazole and echinocandins were investigated through sequencing of the ERG11 and FKS1 genes. Additionally, whole-genome sequencing was performed on echinocandin-resistant and echinocandin-sensitive isolates to analyse genetic homology among the strains.ResultsAll the strains were classified into two genetic clades, clade I and clade III, and all exhibited resistance to fluconazole. In the fluconazole-resistant strains, the amino acid substitutions Y132F and VF125AL were identified in the ERG11 gene. The resistance rates to caspofungin, micafungin, and anidulafungin were 7.4, 7.4, and 3.7%, respectively. Among the eight echinocandin-resistant strains, amino acid substitutions (S639Y, W691L, and S639F) were found within the HS1 hotspot region of the FKS1 gene. A phylogenetic tree was constructed on the basis of 403 SNPs and revealed two major clusters: Cluster A and Cluster B. Cluster A included the 16 isolates analyzed in this study. Cluster B consisted of 12 reference isolates retrieved from publicly available genomic databases.ConclusionGenetic clade I and clade III C. auris strains are prevalent in southern China and present high levels of resistance to fluconazole. Controlling the spread of C. auris in this region presents significant challenges for public health management.